Earth’s crust composition of the Ingul megablock of the Ukrainian Shield (types of crust) and patterns of location of ore mineral resources - V. I. Starostenko; P. Ya. Kuprienko; I.B. Makarenko; A. Savchenko; O.V. Legostaeva (Геофизический журнал, 2017)
Within the Ingul Megablock of the Ukrainian Shield, according to the data of three-dimensional density modeling, at the scale of 1 : 200 000, the thickness of conditionally allocated “granite”, “diorite”, “basalt” layers, which abroad have the name of the upper, middle and lower crust, are determined and their characteristic is given. In relation to the thickness of each layer to the total crust, which is expressed in parts, four types of crust are distinguished: granite, diorite, leuco-basalt, basalt. Since the composition of the Earth’s crust is an important factor in assessing the prospects for minerals, a comparison of the location of the ore deposits of manifestations of hydrothermal and hydrothermal-metasomatic genesis with a real composition scheme is made. It is established that most of the deposits of minerals are confined to blocks of granitic-diorite and diorite types of crust, and the smaller — gravitates to blocks of leuco-basalt and basalt types.